ANALISIS KEBIJAKAN WALI KOTA PROBOLINGGO DALAM PELAKSANAAN PEMBINAAN KEPEGAWAIAN DI LINGKUNGAN PEMERINTAHAN KOTA PROBOLINGGO - Mubaroq, Husni; Watoni, Sohibul; Hasanah, Zairotul (Universitas Panca Marga, 2021)
The concept of decentralization is the authority of the government that is delegated to the regions, including the authority of personnel in accordance with the decentralized functions. The regional head has the task of being a coach of the State Civil Apparatus in the concept of decentralization. There was a case that the Mayor of Probolinggo issued a decree to remove Tutang Heri Aribowo, who served as an Expert Staff at the Regional Secretariat of the City of Probolinggo. The Regional Government as a civil servant coach tends to abuse its authority. This happens because there is the influence of the political elite in giving disciplinary punishment to employees. The author wants to describe the problem in a study that uses descriptive analytical methods, namely descriptions of the facts and characteristics of a particular population or area in a systematic, factual and thorough manner. The data in this study collected materials by means of a library study. This study also uses a normative juridical method with a statutory approach. So that in this study we know the legal basics of this problem. In order to know the proper process and institution related to the case problem. This aims at employee disputes on the right track and there is no arbitrariness by the ASN supervisor. Keywords: Employment Disputes, Authority, Personnel Advisor